Legal support for innovation activity - Tkachоv, M. M.; Tkachоva, N. P. (WSEH, 2025)
Legal support for innovation activity is a fundamental prerequisite for fostering technological progress and ensuring effective commercialization of research outcomes. It encompasses the development of regulatory frameworks, protection of intellectual property rights, and facilitation of contractual relations between innovators, enterprises, and investors. By establishing clear legal mechanisms for patenting, licensing, and technology transfer, legal support reduces risks, enhances transparency, and promotes fair competition. Furthermore, it contributes to the creation of innovation-friendly environments, strengthens international cooperation, and ensures compliance with national and global standards. The paper highlights the role of legal instruments in safeguarding innovative outputs and enabling sustainable economic growth.
Keywords: legal support; innovation activity; globalization; digital transformation; economic development; economies; intellectual property; technology transfer; licensing; patenting; regulatory framework; commercialization